2018
DOI: 10.2147/ijwh.s172696
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for insufficient endometrial tissue from endometrial sampling

Abstract: ObjectiveTo assess the incidence of and factors that predict insufficient tissue after endometrial sampling.MethodsThis study reviewed the records of women undergoing endometrial sampling at Khon Kaen University’s Srinagarind Hospital between June 2014 and June 2015. It excluded cases in which the device could not be inserted into the uterine cavity due to pain intolerance or equipment failure. The criterion for diagnosing insufficient endometrial tissue was a lack of any intact tissue fragments containing bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 17 publications
3
21
1
3
Order By: Relevance
“…Consistent with our findings, several authors reported that the chance of getting an adequate sample was increased in postmenopausal women with an endometrial thickness of >12 mm, and they also suggested that nulliparity and advanced age were independent factors affecting unsuccessful Pipelle sampling (15). A recent study reported that an endometrial thickness of less than 8 mm and menopausal status were associated with an increased risk of insufficient endometrial sampling (19).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, several authors reported that the chance of getting an adequate sample was increased in postmenopausal women with an endometrial thickness of >12 mm, and they also suggested that nulliparity and advanced age were independent factors affecting unsuccessful Pipelle sampling (15). A recent study reported that an endometrial thickness of less than 8 mm and menopausal status were associated with an increased risk of insufficient endometrial sampling (19).…”
Section: Discussionsupporting
confidence: 90%
“…Combining both inadequate and inconclusive reports in our study sample inadequacy was higher in the current study compared to all other publications which might be because of less endometrial assessment by transvaginal ultrasound. Retrospective review at the Khon Kaen University’s Srinagarind Hospital showed menopausal status and endometrial thickness of less than 8 mm were independent predictors for insufficient endometrial tissue after endometrial sampling(21). In our study patients ≥ 50 years of age were eight times more likely to have inadequate sample compared to those 20-29 years of age but TVUS was not done to assess endometrium in almost all cases (97.74%) and there is no association with parity and level of health professional who did the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…U literaturi jako varira postotak nezado voljavajućih uzoraka: od 6 pa do 44,5% za histološku dijagnozu asimptomatskih žena. 21 Ovdje izloženi re zultati za citološke i histološke uzorke spadaju u sku pinu istraživanja s manjim postotkom nezadovoljava jućih uzoraka, vjerojatno zato što su istraživanje pro veli iskusni patolozi i citolozi iz iste institucije i prema standardiziranim kriterijima za procjenu prikladnosti uzoraka.…”
Section: Raspravaunclassified
“…Slične probleme navode i drugi autori. 21,24,28,29 Jedno stavna hiperplazija endometrija točno je dijagnostici rana kod 11 od 13 bolesnica (84,6%), a kompleksna hiperplazija samo u njih 50% (2/4) (slika 3.). Katkad se degenerativne promjene endometrijskih stanica poput, npr., povećanja jezgara mogu interpretirati kao atipija.…”
Section: Raspravaunclassified
See 1 more Smart Citation